Ovicidal and repellent activities of several plant essential oils against Periplaneta americana L. and enhanced activities from their combined formulation - Mayura Soonwera; Tanapoom Moungthipmalai; Wacharaporn Takawirapat; Sirawut Sittichok (My University, 2022)
Abstract Natural ovicidal and repellent agents against Periplaneta americana L. are urgently needed, and plant essential oils (EOs) can assume this role quite readily. In this study, ovicidal and repellent activities against Periplaneta americana of EOs from Cymbopogon citratus (Stapf.), Cinnamomum verum (J. Presl.), Eucalyptus globulus (Labill.), Illicium verum (Hook.f.), and Zanthoxylum limonella (Alston) in soybean oil and in ethyl alcohol were determined by topical and dual-choice assays, as well as 10% cypermethrin and a combined formulation of 5% C . verum EO + 5% I . verum EO. Cypermethrin at 10% provided the highest toxicity (100% inhibition rate) against the eggs, but only slightly higher than that (99.3%) provided by the combined EO formulation, while the highest repellent activity against the adults was provided by the combined formulation (89.5% repelled cockroaches at 48 h after treatment). In addition, all EO formulations in soybean oil provided higher ovicidal and repellent activities than those in ethyl alcohol. To conclude, the combined EO formulation in soybean oil can replace cypermethrin because their efficacy was nearly equivalent, but the combination should be much safer to use.
Keywords: Eucalyptus globulus; DEET; Eucalyptus oil; Insect Pest Control Strategies